2017
DOI: 10.1108/dlp-07-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

A survey of digital information literacy (DIL) among academic library and information professionals

Abstract: Purpose The key purpose of this study is to explore digital information literacy (DIL) possessed by South Valley University (SVU) library and information professionals. It also tries to identify the various types of DIL and find constraints affecting the related skills and competencies of those professionals. Design/methodology/approach A quantitative research methodology was adopted in the form of a survey, which was undertaken from February to March 2016. As stated by Kerlinger (1986), the survey research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 13 publications
6
38
2
1
Order By: Relevance
“…Simard and Karsenti, 2016), physical facilities, internet connectivity and e-databases subscription (e.g. Mansour, 2016). Some scholars investigated this issue from the perspective of individual characteristics, such as internet experience and individual education (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Simard and Karsenti, 2016), physical facilities, internet connectivity and e-databases subscription (e.g. Mansour, 2016). Some scholars investigated this issue from the perspective of individual characteristics, such as internet experience and individual education (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars investigated this issue in terms of social support such as training (e.g. Mansour, 2016). But there are few studies on the influencing factors of mobile internet literacy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan and Bhatti (2017) concluded that the university librarians working in Higher Education Commission (HEC)-recognized universities in Punjab province of Pakistan possess basic level of digital competencies for developing and managing digital libraries. Regarding librarians' knowledge-based competencies, as well as skills-based competencies, especially when these competencies related to the integration of ICTs into the library work, the study by Mansour (2017) showed that such kind of competencies possessed by South Valley University (SVU) library and information professionals ranged between competent and somewhat competent.…”
Section: Knowledge Based Competencies Among Librariansmentioning
confidence: 99%
“…In addition, there is a lack of direct channels between multi-source L&I resource platforms. It is time-consuming to browse and acquire knowledge on multiple platforms [15][16][17]. Many scholars have explored the ways to aggregate the knowledge in L&I resources, aiming to scientifically organize, mine, and manage the knowledge, and to innovate the knowledge service model [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%